ANALISIS EFISIENSI ALAT TANGKAP CANTRANG DI KABUPATEN PEMALANG, JAWA TENGAH - -, WARIDIN (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol. 6, No. 3 November 2006, 2012)
Objective of this research are to analyze of efficiency (technique, alocative and economics) and to analyze return and expenditure on fish catching enterprise with use cantrang catch tool in Fish Trade Center (Tempat Pelelangan Ikan, TPI) at Asemdoyong, Pemalang Regency, Central Java. Use the simple random sampling methods; choose 100 fisherman people as respondent. The analysis of data with stochastic frontier production function using the Maximum Likelihood Estimation (MLE) Method. The result of estimation shows that majority fish catching enterprise use the Cantrang catching tools, partly (50-90^) achieved technical efficiency. Average value of technical efficicieny is 0.619. Price and economic efficiency value each 1,612 and 1,922. Technically and economically, fish catching enterprise use the catrang tool not efficiency yet, so that still probably increase or decrease production input allocation. Result of the study so indicate that the enterprise that done by fisherman still profitable like indicate by ratio value of return cost ratio is 1,18.
Keywords: Production, Frontier, Efficiency Technique, Alocative,Economics PENDAHULUAN Latar Belakang